Solving Two Dimensional Coupled Burger’s Equations and Sine-Gordon Equation Using El-Zaki Transform-Variational Iteration Method - H. Al-Tai, Marwa; Al-Fayadh, Ali (Al-Nahrain Journal of Science, 2021)
In this paper, the combined form of the Elzaki transform and variation iteration method is implemented efficiently in finding the analytical and numerical solutions of the two-dimensional nonlinear coupled Burger’s partial differential equations and sine-Gordon partial differential equation. The obtained solutions were compared to the exact solutions and other existing methods. Illustrative examples show the efficiency and the power of the used method.